2018
DOI: 10.5812/intjssh.79463
|View full text |Cite
|
Sign up to set email alerts
|

EMG Analysis of Trunk and Lower Limb Muscles in Three Different Squat Exercises in Athletes and Non-Athletes

Abstract: Objectives: Squat is known as a common and functional exercise for strengthening the lower limb muscles. However, researchers put it in the category of exercises with high risk of injury. So, the purpose of this study was to investigate the effect of three different techniques of squat on electromyographic response of trunk and lower limb muscles in athletes and non-athletes. Methods: Twenty subjects including 10 amateurs and 10 professional athletes ranging from 22 to 27 years old participated in the study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The use of supplements to enhance sports performance and prevent injuries has become a contemporary area of interest in the pursuit of athletic success (20)(21)(22). Cycling, in particular, is a sport that is highly susceptible to sports injuries due to prolonged periods of high-intensity exercise (23).…”
Section: Discussionmentioning
confidence: 99%
“…The use of supplements to enhance sports performance and prevent injuries has become a contemporary area of interest in the pursuit of athletic success (20)(21)(22). Cycling, in particular, is a sport that is highly susceptible to sports injuries due to prolonged periods of high-intensity exercise (23).…”
Section: Discussionmentioning
confidence: 99%
“… Da et al (2007) showed that vibration training increased oxygen uptake by 17% compared to non-vibration training. The squat, as an essential compound exercise in strength training, is crucial to the physiological function and athletic performance of athletes ( Salmanpour, 2022 ), which can increase muscle strength ( Taheri, 2018 ), endurance, and explosive power, and also effectively improve the body’s reaction time ( Taheri, 2017 ) and adaptive ability and prevent sports injuries ( Al-Azzawi et al, 2023 ). Therefore, by understanding the effects of vibration training on energy metabolism in squatting ( Hibino et al, 2023 ), we can integrate vibration training into athletes’ strength training programs and the general public’s sports and fitness ( Dos Santos et al, 2023 ), and maximize the optimization of athletes’ training effects and the development of more personalized training programs by enhancing energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…Static and dynamic balance were measured by the Borg Fatigue Scale and measured before and after open and closed chain fatigue protocol. Fifteen in Borg scale shows 75% to 85% of the maximum oxygen consumption, considered approximately as the threshold of lactate (14). Static and dynamic balance were measured using the Balance Error Scoring System (BESS) the Star Excursion Balance test (SEBT) in eight directions respectively (11,15).…”
Section: Introductionmentioning
confidence: 99%
“…One-repetition maximum (1RM) was used by Equation 1. 60% of 1RM was intervened in both OKC and CKC as exercise intensity (14,16).…”
Section: Introductionmentioning
confidence: 99%